Morpho-phylogenetic characterizations reveal a new species of Coccomyces on Cunninghamia lanceolata from China - Zheng, Lu; Tang, Mingxia; Li, Yinlong; Li, Xinyuan; Wang, Shijuan (Phytotaxa, 2024)
Specimen of Coccomyces collected on Cunninghamia lanceolata, from Huangshan Mountain in Anhui Province, China, was identified as a new species, named here as Coccomyces cunninghamiae. Although multi-gene (ITS, nrLSU, mtSSU) phylogenetic analysis showed that the new species was closely related to C. anhuiensis, it differs significantly from C. anhuiensis in morphology by intraepidermal or subepidermal ascomata, well-developed paraphyses forming epithecium and shape of ascospores. Moreover, the ITS sequence similarity between them is only 87.86%. Specimens studied are deposited in the Reference Collection of Forest Fungi of Anhui Agricultural University, China (AAUF).